Acquisition of Adverbs and Pronominal Adverbs in Melayu Batu Bara Child - Latifah Aini; Salamuddin Salamuddin; Yulia Arfanti (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
This article addresses the acquisition of adverbs in a Melayu Batu Bara monolingual boy from speech onset until age 6. This research is based on analysis of authentic material: a corpus of transcription of audio recordings of the child in verbal interaction with adults, and diary records. The acquisition sequence and adverbial type frequency were analyzed. The boy acquired adverbs of place first; although direction was acquired before location, location became more frequent. Adverbs relating to time were developed second, and location in time and repetition were the most frequent temporal aspects. Adverbs of degree followed; adverbs related to high degree were more frequently expressed than adverbs related to low degree. Adverbs of manner appeared last, in which adverbs related to a broader evaluative sense prevailed. Adverbs related to cause were manifested mostly by the interrogative mengapo/ why. Interrelation between the acquisition of nominal and verbal categories was found: when the child acquired the category of nominal case and was able to use the construction of preposition + noun, the percentage of adverbs of place decreased. When he acquired the verbal aspect, the percentage of adverbs related to time decreased.